Leveraging TOGAF ADM for Enterprise Architecture in West Seram Environment Agency - Lesnussa, Johanis; Sitokdana, Melkior N. N. (Journal of Information System and Informatics, 2023)
Despite its critical role in environmental governance, the West Seram Environment Agency in Maluku has yet to fully integrate information systems (IS) and information technology (IT) into its operational processes. Recognizing the pivotal role of IS/IT in enhancing organizational efficiency and effectiveness, this study proposes an innovative enterprise architecture planning approach to facilitate IS/IT development within the agency. Employing a qualitative research methodology, the study utilizes The Open Group Architecture Framework (TOGAF) Architecture Development Method (ADM). This method concentrates on three key domains: business architecture, information systems architecture, and technology architecture. The results of this research offer a suite of IS/IT solutions tailored to the agency's needs. These include the strategic recruitment and development of appropriate work systems, implementation of comprehensive IS/IT work plans, advanced data processing techniques, creation of digital-based applications, and the design and implementation of efficient network topologies. These solutions are poised to revolutionize the agency's operations, significantly enhancing its capacity for environmental management and governance.